2008
DOI: 10.1123/jsr.17.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Physical Therapy Treatments on Lateral Epicondylitis

Abstract: There are numerous treatments for lateral epicondylitis and no single intervention has been proven to be the most efficient. Therefore, future research is needed to provide a better understanding of beneficial treatment options for people living with this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 25 publications
0
27
0
2
Order By: Relevance
“…Ten [57][58][59]61,62,65,68,70,79,84 of the 29 studies identified in the current review were also included in the review by Bisset et al 80 Evidence from these 10 studies was evaluated in the overview by Bisset et al; 80 a summary of recommendations from the overview is given in Table 31. We compare our results against these recommendations in Chapter 4, Current clinical effectiveness evidence in context.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Ten [57][58][59]61,62,65,68,70,79,84 of the 29 studies identified in the current review were also included in the review by Bisset et al 80 Evidence from these 10 studies was evaluated in the overview by Bisset et al; 80 a summary of recommendations from the overview is given in Table 31. We compare our results against these recommendations in Chapter 4, Current clinical effectiveness evidence in context.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…injection, medication, rest, ice, bracing, therapeutic modalities, therapeutic exercise, massage, mobilization and manipulation. [10][11][12][13][14][15][16][17] This deficit could be a plausible explanation for research indicating that there is no significant long-term benefit of conservative treatment when compared to a wait and see appro ach. 10,13,17 The use of specific patho-anatomic diagnoses in patients with spinal conditions has also shown unacceptable levels of reliability.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical assessment instruments used to assess functional progress during wrist and forearm rehabilitation, forearm strength contributes up to 25% of the overall functional assessment (Souer, LozanoCalderon, & Ring, 2008). Thus, forearm pronation and supination strength are integral parts of the rehabilitation of people with elbow disorders, such as lateral epicondylitis (Alizadehkhaiyat et al, 2007;Erak, Day, & Wang, 2004;Kohia et al, 2008), rheumatoid arthritis (Shigeyama, Inoue, Hashizume, Nagashima, & Senda, 1997), forearm fractures (Dubberley, Faber, MacDermid, Patterson, & King, 2006;Droll et al, 2007;Souer et al, 2008), and nerve impairment (Rainville, Noto, Jouve, & Jenis, 2007;Rosén, Dahlin, & Lundborg, 2000) as well as the development of baseball (Szymanski, Szymanski, Molloy, & Pascoe, 2004) and tennis athletes (Alizadehkhaiyat et al, 2007;Ellenbecker, Roetert, & Riewald, 2006).…”
mentioning
confidence: 99%
“…Forearm strength assessment has often been limited to grip strength (Kohia et al, 2008;Rosén et al, 2000). When forearm pronation and supination have been assessed, a variety of methods have been used, including manual muscle tests (Rainville et al, 2007), weight-lifting maximum repetitions (Szymanski et al, 2004), research torque cells devices (Matsuoka, Berger, Berglund, & An, 2006;O'Sullivan & Gallwey, 2005;Shigeyama et al, 1997), work simulators (Droll et al, 2007;Dubberley et al, 2006), and isokinetic rehabilitation and assessment devices such as the Cybex 6000 (Ellenbecker et al, 2006).…”
mentioning
confidence: 99%